ПИТАННЯ САМООЦІНКИ В КОНТЕКСТІ ОРГАНІЗАЦІЇ САМОСТІЙНОЇ НАВЧАЛЬНОЇ ДІЯЛЬНОСТІ СТУДЕНТІВ ВИЩИХ ПЕДАГОГІЧНИХ НАВЧАЛЬНИХ ЗАКЛАДІВ (Педагогіка вищої та середньої школи, 2008)
The article reveals the role and influence of self-evaluation in the process of organizing and realizing self directed learning activities by students of higher teacher training institutions.